Evaluating performance of post-tensioned steel connections with strands and reduced flange plates. - Chou, Chung-Che
The seismic performance of post-tensioned steel connections for moment-resisting frames was examined experimentally and analytically. Cyclic tests were conducted on three full-scale subassemblies, which had two steel beams post-tensioned to a concrete-filled tube (CFT) column with high-strength strands to provide recentring response. Reduced flange plates (RFPs) welded to the column and bolted to the beam flange were used to increase the dissipation of energy. Test results indicated that (1) the proposed buckling-restrained RFP could dissipate energy in axial tension and compression, (2) the subassemblies could reach an interstorey drift of 4% without strength degradation, and (3) buckling of the beam occurred towards an interstorey drift of 5%, causing a loss of the strand force, the recentring response, and the moment capacity. A general-purpose non-linear finite element analysis program (ABAQUS) was used to perform a correlation study. The behaviour of the steel beam under both post-tensioning and flexural loadings was compared to the test results and predictions.
Keywords: Post-tensioned steel connections; Strands; Reduced flange plates; Cyclic tests; Finite element analysis